Fibroblasts in fibrosis: novel roles and mediators - Kendall, Ryan T.; Feghali-Bostwick, Carol A. (Frontiers in Pharmacology, 2014)
Fibroblasts are the most common cell type of the connective tissues found throughout the body and the principal source of the extensive extracellular matrix (ECM) characteristic of these tissues. They are also the central mediators of the pathological fibrotic accumulation of ECM and the cellular proliferation and differentiation that occurs in response to prolonged tissue injury and chronic inflammation. The transformation of the fibroblast cell lineage involves classical developmental signaling programs and includes a surprisingly diverse range of precursor cell types—most notably, myofibroblasts that are the apex of the fibrotic phenotype. Myofibroblasts display exaggerated ECM production; constitutively secrete and are hypersensitive to chemical signals such as cytokines, chemokines, and growth factors; and are endowed with a contractile apparatus allowing them to manipulate the ECM fibers physically to close open wounds. In addition to ECM production, fibroblasts have multiple concomitant biological roles, such as in wound healing, inflammation, and angiogenesis, which are each interwoven with the process of fibrosis. We now recognize many common fibroblast-related features across various physiological and pathological protracted processes. Indeed, a new appreciation has emerged for the role of noncancerous fibroblast interactions with tumors in cancer progression. Although the predominant current clinical treatments of fibrosis involve nonspecific immunosuppressive and anti-proliferative drugs, a variety of potential therapies under investigation specifically target fibroblast biology.